2004
DOI: 10.1182/blood.v104.11.3768.3768
|View full text |Cite
|
Sign up to set email alerts
|

Study on Hepatitis C Treatment Using Ribavirin and Pegylated Interferon in Thalassemia Patients (SCRIPT): One Year Report.

Abstract: BACKGROUND: Treatment of thalassemia patients with HCV using combination interferon and ribavirin is limited to few case series. DESIGN: Multicenter randomized single-blinded trial comparing PEG-IFN a-2a +/− ribavirin in thalassemia major patients with chronic HCV. METHODS: 20 patients with HCV genotypes 1 and 4 were randomized into Group A (PEG-IFN 180 mg SC once weekly) and B [PEG-IFN and ribavirin (≥10.6 mg/kg/d)] for 48 weeks. Baseline studies included liver biopsy (histology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One study was excluded because it did not provide enough information on methodology and outcome [13], one further study was excluded because it just reported early viral response [14] and two other studies were excluded because they did not report SVR [15,16]. Four duplicate publications of the same patients’ data as seminar proceedings were also excluded from analysis [17–20]. Two further studies were excluded because they defined complete, partial and non‐response according to ALT level at the end of treatment [21,22], one conference proceedings in Italian language were also excluded [23].…”
Section: Resultsmentioning
confidence: 99%
“…One study was excluded because it did not provide enough information on methodology and outcome [13], one further study was excluded because it just reported early viral response [14] and two other studies were excluded because they did not report SVR [15,16]. Four duplicate publications of the same patients’ data as seminar proceedings were also excluded from analysis [17–20]. Two further studies were excluded because they defined complete, partial and non‐response according to ALT level at the end of treatment [21,22], one conference proceedings in Italian language were also excluded [23].…”
Section: Resultsmentioning
confidence: 99%
“…Previously in a meta-analysis of literature, we showed that peginterferon monotherapy can induce a SVR rate of 28 percent in thalassemia major patients, while combination therapy of peginterferon and ribavirin (low dose therapy, accompanying by tight monitoring of patients) elicits a SVR rate of 44 percent [ 20 ]. The small sample size and lack of control group in included studies were two major downsides of our meta-analysis [ 21 ][ 22 ][ 23 ][ 24 ][ 25 ][ 26 ]. Indeed, this study has been designed to address this issue and to reach a more precise estimation of ribavirin tolerability and the effect of its low dose administration on improving SVR in HCV infected thalassemia major patients.…”
Section: Introductionmentioning
confidence: 99%